Cross-Religious Political Communication: Christian Candidates and Muslim Voters in Papua’s 2024 Election - Abdul Qadir, Abdul Qadir; Imam Alfian Kadir (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
This study analyzes the political communication strategy in the 2024 Papua Gubernatorial Election, focusing on the cross-religious approach employed by the Benhur Tomi Mano (BTM) and Yeremias Bisai pair. Specifically, this research examines how a Christian candidate navigates political marketing within a Muslim-minority context through the